2018
DOI: 10.1039/c8cc06807k
|View full text |Cite
|
Sign up to set email alerts
|

Cp*Co(iii)-Catalyzed oxidative [5+2] annulation: regioselective synthesis of 2-aminobenzoxepines via C–H/O–H functionalization of 2-vinylphenols with ynamides

Abstract: A Cp*Co(iii)-catalyzed [5+2] C-H annulation reaction of 2-vinylphenols with ynamides was developed. The reaction led to the efficient synthesis of valuable 2-aminobenzoxepines in high regioselectivity. Mild reaction conditions, good functional group tolerance, and moderate to good yields were observed. The synthetic utility was demonstrated by a gram-scale synthesis and further transformations of the products. Preliminary mechanistic studies were conducted, and a possible catalytic cycle was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Han et al in 2018 reported the synthesis of 2‐aminobenzoxepines 352 through cobalt‐catalyzed oxidative [5 + 2] C–H annulation of 2‐vinylphenols 188 with ynamides 351 (Scheme 77). [ 115 ] The use of cobalt as an inexpensive and environmentally friendly transition metal catalyst for the C–H activation, high regioselectivity, good functional group tolerance, mild reaction conditions, moderate to good yields of 2‐aminobenzoxepine derivatives 352 , and reaction extend in practical gram scale are the advantages of the described approach. Based on the cobalt(III) chemistry and previous obtained results, a proposed catalytic cycle is outlined in Scheme 78.…”
Section: Cobalt‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…Han et al in 2018 reported the synthesis of 2‐aminobenzoxepines 352 through cobalt‐catalyzed oxidative [5 + 2] C–H annulation of 2‐vinylphenols 188 with ynamides 351 (Scheme 77). [ 115 ] The use of cobalt as an inexpensive and environmentally friendly transition metal catalyst for the C–H activation, high regioselectivity, good functional group tolerance, mild reaction conditions, moderate to good yields of 2‐aminobenzoxepine derivatives 352 , and reaction extend in practical gram scale are the advantages of the described approach. Based on the cobalt(III) chemistry and previous obtained results, a proposed catalytic cycle is outlined in Scheme 78.…”
Section: Cobalt‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…However, the construction of medium heterocyclic rings via dehydrogenative cobalt‐catalyzed C−H/Het−H functionalization has not been documented until recently. In 2018, the cobalt‐catalyzed [5+2] oxidative annulation was achieved by the Li group (Scheme ) . 2‐Vinylphenol 25 derivatives and ynamides 26 could be transferred efficiently in the presence of Ag 2 CO 3 and Cu(OAc) 2 ⋅H 2 O as oxidants under extremely mild conditions and at room temperature.…”
Section: Alkyne Annulationmentioning
confidence: 99%
“…101 Meanwhile, The Li group developed a straightforward synthesis of 2-aminobenzoxepines from ynamides using cobalt catalyst (Scheme 23c). 102…”
Section: Benzoxepinesmentioning
confidence: 99%